Political discourse and media in times of crisis - Iordanidou, Sofia; Jebril, Nael, 1980-; Takas, Emmanouil (Anthem global media and communication studies., 2023)
This edited book examines the key challenges in political discourse and journalistic practice in times of crises. It focuses on European paradigms and links political rhetoric and media challenges with the societal, political, and financial crises from 2008 until the present.